Emergence of deep convection in the Arctic Ocean under a warming climate - Lique,C; Johnson,HL; Plancherel,Y (Climate Dynamics, 2018)
The appearance of winter deep mixed layers in the Arctic Ocean under a warming climate is investigated with the HiGEM coupled global climate model. In response to a four times increase of atmospheric CO2 levels with respect to present day conditions, the Arctic Basin becomes seasonally ice-free. Its surface becomes consequently warmer and, on average, slightly fresher. Locally, changes in surface salinity can be far larger (up to 4 psu) than the basin-scale average, and of a different sign. The Canadian Basin undergoes a strong freshening, while the Eurasian Basin undergoes strong salinification. These changes are driven by the spin up of the surface circulation, likely resulting from the increased transfer of momentum to the ocean as sea ice cover is reduced. Changes in the surface salinity field also result in a change in stratification, which is strongly enhanced in the Canadian Basin and reduced in the Eurasian Basin. Reduction, or even suppression, of the stratification in the Eurasian Basin produces an environment that is favourable for, and promotes the appearance of, deep convection near the sea ice edge, leading to a significant deepening of winter mixed layers in this region (down to 1000 m). As the Arctic Ocean is transitioning toward a summer ice-free regime, new dynamical ocean processes will appear in the region, with potentially important consequences for the Arctic Ocean itself and for climate, both locally and on larger scales.